Observational study to determine the utility of hospital administrative data to support case finding of English patients at higher risk of severe healthcare-related harm. Issue 6 (21st June 2019) - Hogan, Helen; Cooke-O'Dowd, Nora; Chattopadhyay, Kaushik; van der Meulen, Jan; Sherlaw-Johnson, Christopher; Black, Nick
Abstract : Objectives: To identify ways of using routine hospital data to improve the efficiency of retrospective reviews of case records for identifying avoidable severe harm Design: Development and testing of thresholds and criteria for two indirect indicators of healthcare-related harm (long length of stay (LOS) and emergency readmission) to determine the yield of specified harms coded in Hospital Episode Statistics (HES). Setting: Acute National Health Service hospitals in England. Participants: HES for acute myocardial infarction (AMI), bowel cancer surgery and hip replacement admissions from 2014 to 2015. Interventions: Case-mix-adjusted linear regression models were used to determine expected LOS. Different thresholds were examined to determine the association with harm. Screening criteria for readmission included time to readmission, length of readmission and diagnoses in initial admission and readmission. The association with harm was examined for each criterion. Results: The proportions of AMI cases with a harm code increased from 14% among all cases to 47% if a threshold of three times the expected LOS was used. For hip replacement the respective increase was from 10% to 51%. However as the number of patients at these higher thresholds was small, the overall proportion of harm identified is relatively small (15%, 19%, 9% and 8% among AMI, urgent bowel surgery, elective bowel surgery and hip replacement cohorts, respectively). Selection of the time to readmission had an effect on the yield of harms but this varied with condition. At least 50% of surgical patients had a harm code if readmitted within 7 days compared with 21% of patients with AMI. Conclusions: Our approach would select a substantial number of patients for case record review. Many of these cases would contain no evidence of healthcare-related harm. In practice, Trusts may choose how many reviews it is feasible to do in advance and then select random samples of cases that satisfy the screening criteria.